Czy zakażenie Helicobacter pylori ma związek z występowaniem idiopatycznej centralnej chorioretinopatii surowiczej? - Kmera-Muszyńska, Maria; Wójcicka, Izabella; Muszyński, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Upper gastrointestinal tract endoscopy was performed in 14 patients with clinically determined central serous chorioretinopathy to detect eventual Helicobacter pylori infection. In 11 patients Helicobacter pylori infection was detected using urease test and histopathological examination. Obtained results confirm suggestions that Helicobacter pylori infection may be a factor associated with CRS etiopathogenesis. To understand those correlations large studies and large patients population are to be performed.